EVALUASI POLA SIRKULASI PENUMPANG DAN KINERJA PARKIR, STUDI KASUS : STASIUN CIMAHI - Erlianna; Dian Nurdiani; Khairinissa Zakwani; Novida Dinayazni Pelu; Raisya Pasha Amellia (Universitas Widyatama, 2025)
Transportation is the movement of people or goods from place to place and has two types of land and sea transport. Land transportation includes road transport, such as cars, buses, and motorcycles, as well as trains. One part of land transport is the public transport terminal, the railway station. The railway station serves as a stop or transit point for passengers built to meet the needs of passengers. According to the Directorate General of Railways, existing railway stations in Indonesia can be categorized by class and function. Cimahi Station is a type C station located in Baros Village, Central Cimahi District, Cimahi City, West Java. There are several factors that can affect the performance of stations that provide good facilities and services. The influencing factors are convenience, safety, accessibility, and ease of the station. Thus, in this study, it will discuss passenger circulation patterns, vehicle circulation patterns, parking area conditions, and parking performance at Cimahi Station. The research methodology used is observation and questioning of Cimahi Station users. The result was found that the passenger circulation pattern was a linear pattern, while for the vehicle circulation pattern there was one entrance and exit at the station. The layout of passenger and vehicle circulation patterns is described using AutoCAD. The condition of the parking area at Cimahi Station is used only for two- and four-wheeled vehicles, but the parking capacity of car users is less than that of motorcycle users. And also in the parking performance of Cimahi Station has different perceptions from car and motorbike users. In terms of convenience, convenience, safety, and accessibility factors for motorbike users, the value is higher than that of car users.